ANALISIS KONFLIK ANTARA MASYARAKAT, PEMERINTAH DAN SWASTA - Irwandi Irwandi; Endah Ratnawaty Chotim (Centre for Asian Social Science Research (CASSR), FISIP, UIN Bandung, 2017)
This paper describes the chronology of the conflict, the factors that cause conflict, the form of conflict and conflict resolution between society, government and sand mining companies in Samak River Village, Samak River Village, Badau District, Belitung Regency. Conflict that occurred in the Samak River Hamlet backdrop by the lack of socialization, less open village government to the community, the difference in the importance of the impact of mining activities. The forms of social conflict that occurred in the Samak River Hamlet are vertical conflicts and horizontal conflicts. Vertical conflicts occur between communities, village governments and mining companies. While horizontal conflicts occur within the society itself between the pro and the opposing groups because of differences of interest. Conflict resolution measures taken by communities, government and mining companies include negotiations; Kosuliasi; Mediation; and Arbitration